2018
DOI: 10.3906/biy-1708-23
|View full text |Cite
|
Sign up to set email alerts
|

Combined extract of Moringa oleifera and Centella asiatica modulates oxidative stress and senescence in hydrogen peroxide-induced human dermal fibroblasts

Abstract: Moringa oleifera Lam. and Centella asiatica (L.) Urb. leaves have been previously reported to exhibit antioxidant activity. The objective of the present study is to determine the in vitro antioxidant activity of the combined extracts of M. oleifera and C. asiatica (TGT-PRIMAAGE) and its effect on hydrogen peroxide (H 2 O 2)-induced oxidative stress in human dermal fibroblasts. TGT-PRIMAAGE acted on the mechanism of hydrogen transfer as it showed scavenging activity in the DPPH assay. This is due to the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Moreover, our evidence suggests that MOe may prevent DEHP-induced mitochondrial damage by stabilizing membrane potential and decreasing caspase activation in the mitochondrion. A recent paper demonstrated that pretreating human neuron cells with MOe showed a significant resistance to H 2 O 2 -induced apoptotic cell death [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our evidence suggests that MOe may prevent DEHP-induced mitochondrial damage by stabilizing membrane potential and decreasing caspase activation in the mitochondrion. A recent paper demonstrated that pretreating human neuron cells with MOe showed a significant resistance to H 2 O 2 -induced apoptotic cell death [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…For establishment of the premature senescence model, hDFs were treated with 50, 100, 200 and 400 μ M H 2 O 2 (in 10% FBS in high glucose DMEM) at 37°C with 5% CO 2 for 1 or 2 h. Cells were then washed with serum-free high glucose DMEM twice to remove residual H 2 O 2 (20,21) and cultured in high glucose DMEM with 10% FBS for 4 days; growth medium changed every 48 h. In the CdM treatment group, H 2 O 2 -treated cells (200 μ M, 1 h) were washed with serum free medium and incubated with CdM for 4 days. To ensure sufficient nutrients were available, CdM was changed every 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…The colour intensity was graded as either very high (++++), high (+++), moderate (++), low (+), or not detected (−) compared to the positive control. The quantitative results were determined as previously described by Hisam et al with slight modification [28]. The absorbance (Wavelength range: 435– 635 nm) was measured by using an ELISA plate reader (Tecan 200, Switzerland).…”
Section: Methodsmentioning
confidence: 99%